Pengungkapan Perbankan Hijau dan Kinerja Bank Syariah di Indonesia: Eksplorasi Hubungan dan Peran Moderasi Regulasi - Siti Khomsatun; Habsyah Fitri Aryani; Adista Ika Pramesti (Owner : Riset dan Jurnal Akuntansi, 2025)
The impact of globalization on economic growth has been predominantly negative, as widely noted. There is a need for environmental responsibility, including within Islamic banking. The environmental responsibility of Islamic banking aligns with the fundamental objectives of Sharia or maqashid sharia. Therefore, the aim of this study is to explore the relation of green banking disclosure and the maqasid shariah performance. The second objective is to investigate the moderating role of regulations on the relation of green banking disclosure and maqashid Shariah performance. This research utilizes 92 observations from 16 Islamic banks from 2017 to 2023, with employing an unbalanced panel data. Moderated regression analysis is conducted for each dimension of green banking disclosure. The findings indicate that green banking disclosure related to employees and customers dimension positively impact on maqashid sharia performance, which is the daily operational dimension of green demonstrates a significant negative. While the policy dimension of green banking shows no effect. Another finding of this study is the absence of evidence for moderation by regulation SEOJK No. 16 of 2021. However, if using 10% significance level, moderation role of regulation indicates that regulations weaken the negative effect of daily operational dimensions on maqashid Sharia performance.